Organisasi Komponen Cadangan Matra Darat - Muradi Muradi (Jurnal Ilmiah Hubungan Internasional, 2013)
The establishment of reserve component becomes an important part in the military system of a state. However, the reserve component in Indonesia is still not clear yet to be established, although, as an organization that has biggest personnel than the others. The Army has an interest to prepare the reserve component for support the regular components of the country's defense. This paper will discuss how the Army reserves component organization established ? How do the composition and the number and distribution of the Army reserve component personnel ? This paper also will examine the possibility of cooperation between the Army and the Local Government in the process of recruitment, maintenance, and deploy of the Army reserves component.Keywords : the Army, the Ministry of Defense, the Reserves Component, the Local Government personnel